A Deep Investigation of Two Poorly Studied Open Clusters Haffner 22 and Melotte 71 in the Gaia era. (1st April 2022) - Bisht, D.; Zhu, Qingfeng; Yadav, R. K. S.; Rangwal, Geeta; Sariya, Devesh P.; Durgapal, Alok; Jiang, Ing-Guey
Abstract: This paper presents a deep investigation of two open clusters, Haffner 22 and Melotte 71, using astrometric and photometric data from Gaia EDR3. We identified 382 and 597 most probable cluster members with membership probability higher than 50%. Mean proper motions in R.A. and decl. are estimated as (−1.631 ± 0.009, 2.889 ± 0.008) and (−2.398 ± 0.004, 4.210 ± 0.005) mas yr −1 for Haffner 22 and Melotte 71, respectively. A comparison of observed CMDs with the theoretical isochrones leads to an age of 2.25 ± 0.25 and 1.27 ± 0.14 Gyr for these clusters. The distances 2.88 ± 0.10 and 2.28 ± 0.15 kpc based on the parallax are comparable with the values derived by the isochrone fitting method. Five and four blue straggler stars (BSS) are identified as cluster members in Haffner 22 and Melotte 71. Based on the relative number of high-velocity (binary) and single stars, we inferred binary fractions for both clusters in the range of ∼10% ≤ f bin ≤ 14%, for both core and o?-core regions. We found binary content is larger in the core region. Mass function slope is in good agreement with the Salpeter's value for Melotte 71 ( x = 1.23 ± 0.38 within mass range 1–3.4 M ⊙ ) while it is quite a flat slope for Haffner 22 ( x = 0.63 ± 0.30 within mass range 1–2.3 M ⊙ ). Evidence for the existence of mass-segregation effect is observed in both clusters. Using the Galactic potential model, Galactic orbits are derived, indicating that both clusters follow a circular path around the Galactic center, evolving slowly.